Equation for solvent activity correlation in ternary solutions with electrolyte and molecular components - Passamonti, Francisco Javier (2015)
An analytical thermodynamically self-consistent equation is proposed for the dependence on composition of the solvent activity of ternary solutions with electrolytic and molecular components (polyols, sugars, etc.). This equation was derived on the basis of the sum of contributions from short and long range interactions to the excess Gibbs free energy of solution. The correlation of experimental data corresponding to 20 aqueous ternary systems was successfully carried out. The results obtained demonstrate an excellent fitting capability of the proposed equation.